2021
DOI: 10.3390/su131810147
|View full text |Cite
|
Sign up to set email alerts
|

School-Aged Students’ Sustainable Online Learning Engagement during COVID-19: Community of Inquiry in a Chinese Secondary Education Context

Abstract: As the COVID-19 pandemic began to spread all over the world, many educational institutions have shifted to a full-time online teaching mode. Although online teaching has been widely explored, the unprecedented initiatives of mass-scale full-time online education at the secondary school level are yet to be unravelled. By using a qualitative approach and drawing on the conceptualisation of learning engagement and Community of Inquire model as conceptual frameworks, this study explored how secondary school studen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 22 publications
(14 citation statements)
references
References 31 publications
(57 reference statements)
2
12
0
Order By: Relevance
“…The literature showed that students in blended learning were more prone to establish a higher level of SoC (Rovai and Jordan, 2004 ). In addition, Chinese technological support and parental involvement may contribute to students' higher level of SoC during the COVID-19 period (Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The literature showed that students in blended learning were more prone to establish a higher level of SoC (Rovai and Jordan, 2004 ). In addition, Chinese technological support and parental involvement may contribute to students' higher level of SoC during the COVID-19 period (Li et al, 2021 ).…”
Section: Discussionmentioning
confidence: 99%
“…The reason might be that video feedback in blended learning offsets the influence of the instructor SP. Yet, the central position of TP in the educational community of inquiry was strengthened by many studies (Hilliard and Stewart, 2019 ; Wang and Liu, 2020 ; Li et al, 2021 ), and so did the association between TP and SP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Gain meaning from the ideas developed during the exploration phase (connecting idea). In general, CoI is tailored for the development of theories of engagement, and can model how learners interact and learn online [10,26]. Many researchers have adopted Garrison's research to identify factual evidence on the relationships that exist between teaching presence, social presence, and cognitive presence [14,[26][27][28].…”
Section: Integrationmentioning
confidence: 99%
“…These issues demand solutions that take the adult learners' needs into consideration. In other words, teachers, peers, and the content need to be effectively incorporated in the virtual learning environment with more engagement and flexibility [9,10]. One popular model that measures these concepts is known as the Community of Inquiry (CoI) model, where engagement and interaction, also known as presence, are adapted.…”
Section: Introductionmentioning
confidence: 99%